Evaluasi Maturitas Manajemen Layanan Infrastruktur Data Center di Dinas Komunikasi dan Informatika Kabupaten Gresik dengan Menggunakan ITIL v.3 Framework - Putri Sari Yasmi; Ismiarta Aknuranda; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Dinas Komunikasi dan Informatika Kabupaten Gresik (Dinas Kominfo) is one of government agencies which is responsible for implementing E-Government based public services. In providing public services and government administration, Dinas Kominfo only provides services in the form of infrastructure and networks, in this case, called a supporting service. Problems found in service operations including the absence of a policy the management of information technology services that resulted in service managers ignoring these important needs and influencing the value of services, the ability of human resources in the field of IT is inadequate. Limited resources in carrying out all assigned tasks and functions result in gaps in other tasks. The thing that becomes a common focus is management commitment is needed to improve service quality. To find out the form of service management, its necessary to evaluate the maturity level of data center infrastructure services. The condition of the data center infrastructure doesn't meet the standards and management of services is not carried out regularly. This evaluation uses the ITIL Framework Domain Service Operation that aims to produce recommendations to improve the management of information technology services. During the evaluation process, data collection was conducted with document studies, interviews, and questionnaires so that a maturity level analysis of 1.26 (initial) was obtained, meaning that there are still many processes for managing data center infrastructure services that haven't been yet implemented and service management functions not clearly defined.